The Relationship between Innovation and Employment in the Peruvian Manufacturing Industry, 2012-2014 - Nolazco Cama, José Luis (2020)
This paper explores the relationship between innovation and employment in the Peruvian manufacturing industry based on the model developed by Jaumandreu (2003) and Harrison et al. (2008) and distinguishes between two types of innovation: product and process. The results show that process innovation reduces the level of employment by an average of 0.45% by replacing employment with more efficient physical capital. However, product innovation is found to increase the level of employment by an average of 0.67%, mainly because a new product is brought to market. The results obtained are robust according to size of firm, the quality structure of the workforce, and technological capacity.